Non-family Employees' Involvement During Product Innovation in Family Firms: A Case Study of Zara Foodstuff Industries Sdn. Bhd. - Kamalol Ariffin, Fadhilah (2010)
With the tremendous growth of family firms and its domination in most countries in the world, innovation is seen as a necessity to ensure their survival in this competitive business world. However, during the process of innovation, the unique characteristic of family firms that consisted of family and non-family employees need to be taken into consideration. Different perspectives and objectives from these two different employees could lead to complexity during such innovation process. This study looked at how far are the involvements of non-family employees during product innovation in a family firm called Zara Foodstuff Industries Sdn. Bhd. The findings from this case study suggests few factors that need to be taken into consideration by family firms such as the relationship between family and non-family employees and the centralized decision-making process. Such characteristics were seen as those that could prohibit the involvement of non-family employees during such innovation process. At the same time, there is also a linkage of cultural factor such as the high power distance that could inhibit such involvement. This paper also presented a series of recommendation that could promote more involvement of non-family employees during product innovation and also possible implication for further studies.